Characterization and tableting properties of microcrystalline cellulose derived from waste paper via hydrothermal method - Riadh Hasan Rana, Md. Sohel Rana, Sabiha Tasnim, Mohammad Rashedul Haque, Shaila Kabir, Md. Shah Amran, Abu Asad Chowdhury (Journal of Applied Pharmaceutical Science, 2022)
Microcrystalline cellulose (MCC) is a popular pharmaceutical excipient, used as a filler or binder in directly compressible tablets, and is the most economical form of all available tablets. In the present research work, we pretreated waste paper with a chelating agent followed by pulping, bleaching, and subsequent hydrothermal degradation with hydrochloric acid at a concentration of 0.5 mol/l and at a 150°C temperature for 120 minutes to produce MCC. The derived MCC was dried at 60°C for 3 hours, ground, and graded into two types based on the particle size. Grade 1 had a particle size of ≤75 microns, while grade 2 had a particle size of 75–125 microns. The derived MCC was chemically identified by an iodinated ZnCl2 solution. Evaluation of the degree of polymerization (DP) and Fourier transforminfrared spectroscopy spectrum further confirmed the identity of the MCC. From the value of intrinsic viscosity of the MCC in cuene, the DP was found to be 126 and 191 for Avicel PH101 and the derived MCC, respectively. The morphological study of derived MCC types by the scanning electron microscopy method suggested that their shapes were very similar to that of Avicel PH101, while the size of MCC grade 1 was very similar to the marketed Avicel PH101. Moreover, the derived MCC types were comparable to the commercial Avicel PH101 based on different physicochemical parameters associated with flow property such as bulk density, tapped density, Hausner’s ratio, Carr’s index, angle of repose, and ash value. The applicability of the derived MCC as a directly compressible excipient was further investigated through the formulation of an uncoated aceclofenac immediate-release tablet. The various tablet parameters like hardness, friability, disintegration, and dissolution time all complied with standard specifications.
Keywords: Microcrystalline cellulose, waste paper, tablet.